Automating inequality : how high-tech tools profile, police, and punish the poor - Eubanks, Virginia, 1972- (St. Martin's Press, 2018)
Eubanks investigates the impacts of data mining, policy algorithms, and predictive risk models on poor and working-class people in America. She shows how automated systems, rather than humans, control which neighborhoods get policed, which families attain needed resources, and who is investigated for fraud. While we all live under this new regime of data, the most invasive and punitive systems are aimed at the poor. -- adapted from jacket.